2017
DOI: 10.1002/cbic.201700467
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement in the Thermostability of a β‐Amino Acid Converting ω‐Transaminase by Using FoldX

Abstract: ω-Transaminases (ω-TAs) are important biocatalysts for the synthesis of active, chiral pharmaceutical ingredients containing amino groups, such as β-amino acids, which are important in peptidomimetics and as building blocks for drugs. However, the application of ω-TAs is limited by the availability and stability of enzymes with high conversion rates. One strategy for the synthesis and optical resolution of β-phenylalanine and other important aromatic β-amino acids is biotransformation by utilizing an ω-transam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…High values have been reported in previous studies using exhaustive mutagenesis with these two methods. 73,74 Figure 2 consistently suggests that the pathogenic mutations generally tend to destabilize the protein. However, the non-pathogenic mutations do the same, and any random mutation is expected to be destabilizing, so the significance of this observation is not evident.…”
Section: Resultsmentioning
confidence: 85%
“…High values have been reported in previous studies using exhaustive mutagenesis with these two methods. 73,74 Figure 2 consistently suggests that the pathogenic mutations generally tend to destabilize the protein. However, the non-pathogenic mutations do the same, and any random mutation is expected to be destabilizing, so the significance of this observation is not evident.…”
Section: Resultsmentioning
confidence: 85%
“…In general the accuracy can be improved additionally, when mutation outliers are eliminated or additional MD-simulations are performed [ 83 ]. FoldX was used successfully in different approaches ( Table 1 ) aiming from enzyme stabilization towards predictions of protein-protein interactions (especially for drug design) or for the prediction of disease-associated mutant proteins, making FoldX a versatile tool for life science [ 81 , [142] , [143] , [144] ].The progress in protein stability prediction is striking, however up to now no in silico calculation can fully spare experimental procedures, although the existing tools can reduce the amount of lab experiments significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the diversity of available algorithms, it seems to be very difficult to choose an efficient tool for protein stabilization. In this review we concentrated on the force field algorithm FoldX, which we have used by ourselves to create a more stable ω-transaminase [ 81 ]. The force field algorithm, which was originally created by Guerois et al became popular as webtool in 2005 by Schymkowitz et al and was refined to the currently last version FoldX 4.0 [ [82] , [83] , [84] ].…”
Section: Un/folding Energy Algorithmsmentioning
confidence: 99%
“…Buß et al . (2018) used Fold-X to predict the ΔΔG value of 8246 single-site mutations of ω-Transaminase to identify the most thermostable variant 45 . See Buß et al .…”
Section: Methodsmentioning
confidence: 99%
“…FoldX force field has been validated on a blind-test database of 625 single-point mutants in 27 simple proteins resulting in a correlation coefficient of 0.73 between predicted and experimental ΔΔG of folding. Several studies had tested the performances of softwares dedicated to the prediction of protein stability 45 , 47 , 48 . For example, Khan and Vihinen (2010) showed that FoldX were one of the most reliable predictors on a set of 1784 single mutations found in 80 proteins with 64% of well prediction 47 .…”
Section: Methodsmentioning
confidence: 99%